2012
DOI: 10.5861/ijrsp.2012.106
|View full text |Cite
|
Sign up to set email alerts
|

Spiritually and mental health among normal and chronic disease group

Abstract: The current study investigates the impact of spirituality on mental health among normal healthy individuals and chronic disease group. This study is based on primary as well as secondary data that has been collected from the various sources. Sample size of the study is 100 respondents (50 normal healthy individuals, 50 chronic disease group individuals). Spirituality assessment Inventory (SAI) and General Health Questionnaire (GHQ) were used for the purpose of data collection. In statistical tools Pearson corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
0
6
2
3
Order By: Relevance
“…Also regarding patients, a study by Fitchett et al (1997), which compared psychiatric patients to other patients, showed that although there are no differences between these two groups as regards spiritual needs, psychiatric patients are reported to have diminished ''spiritual well-being''. In support of these data, a recent study by Sodhi and Manju (2013) that compared chronic patients to healthy individuals concluded that spirituality is significantly correlated with better mental health and that healthy subjects score higher in the spirituality and mental health compared to chronic patients.…”
Section: Spirituality and Mental Healthmentioning
confidence: 82%
“…Also regarding patients, a study by Fitchett et al (1997), which compared psychiatric patients to other patients, showed that although there are no differences between these two groups as regards spiritual needs, psychiatric patients are reported to have diminished ''spiritual well-being''. In support of these data, a recent study by Sodhi and Manju (2013) that compared chronic patients to healthy individuals concluded that spirituality is significantly correlated with better mental health and that healthy subjects score higher in the spirituality and mental health compared to chronic patients.…”
Section: Spirituality and Mental Healthmentioning
confidence: 82%
“…According to them, one can positively enhance the health of a person providing a therapeutic environment that enhances the spiritual beliefs and in such way a positive attitude towards life can be achieved. Spiritual beliefs and practices can be important resources for addressing and positive resolution of chronic disease, and contribute to the mental health of the chronically ill ( 37 ).…”
Section: Spirituality and Health Outcomesmentioning
confidence: 99%
“…The positive influence that spirituality can have in the patients' perception for their health, but also in coping with and adaptation to a serious and life threating illness has been documented by many researches. Specifically, studies that were conducted on patients with diagnosis of serious disease, like cancer in advanced stage, led to the conclusion that spirituality is an important supportive factor that influences both the adaptation to the illness, and the general situation of patients' mental health [20] [21].…”
Section: Introductionmentioning
confidence: 99%
“…A comparative study among healthy and chronically suffering people that was conducted by Sodhi and Manju [21], showed that there is a statistically significant positive correlation among various factors of spirituality and positive mental state. The individuals with a high level of spirituality present higher indicators of mental health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation